A New Selection Procedure For Large Scale Problems - Almomani, Mohammad Hani (2012)

(untitled)
This thesis considers the problem of selecting the stochastic system that has the best (maximum or minimum) expected performance measure when the number of alternatives is finite but large. Ranking and selection procedures have been used successfully for solving problems with small number of alternatives. In order to reduce the computational problem, the idea of ordinal optimization is being used with the objective of finding a good enough system instead of looking for the best system. In this thesis, a new selection approach is proposed for selecting a good system when the number of alternatives is very large.